2018
DOI: 10.1016/j.psychres.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Attempting to discontinue antipsychotic medication: Withdrawal methods, relapse and success

Abstract: Highlights Among 105 people who attempted to stop taking antipsychotic medication, less than half consulted a doctor in preparation and approximately a third used a gradual withdrawal method. Just over half described successfully stopping and half reported no current use.  Unwanted withdrawal effects were reported by 61.9% of the group and spanned emotional, cognitive, physical, and functional domains. Withdrawing gradually across more than one month showed significant, positive associations with self-desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 54 publications
5
18
0
Order By: Relevance
“…The finding that 65% of the current sample reported ‘withdrawal effects’ (self-defined) is similar to a recent finding that 65 of 105 (62%) people trying to come off antipsychotics experienced withdrawal effects [20]. Withdrawal effects can, and should, be distinguished from a relapse of the pre-existing psychosis symptoms [42] so that people can receive the acknowledgement and support they need to gradually come off if they wish to do so [20-22, 42].…”
Section: Discussionsupporting
confidence: 85%
“…The finding that 65% of the current sample reported ‘withdrawal effects’ (self-defined) is similar to a recent finding that 65 of 105 (62%) people trying to come off antipsychotics experienced withdrawal effects [20]. Withdrawal effects can, and should, be distinguished from a relapse of the pre-existing psychosis symptoms [42] so that people can receive the acknowledgement and support they need to gradually come off if they wish to do so [20-22, 42].…”
Section: Discussionsupporting
confidence: 85%
“…27 A research survey also found an association between gradual tapering over a period of 4 weeks or more and self-reported successful discontinuation and absence of relapse. 64 However, another meta-analysis of discontinuation studies did not find any difference in overall relapse rates between studies using abrupt versus gradual discontinuation, also using a definition of gradual as 4 weeks or more (or when depot injection was abruptly stopped). 13 This suggests that this may not be not gradual enough.…”
Section: Overcoming the Barriers To Neuroleptic Discontinuationmentioning
confidence: 96%
“…On the other hand, families, carers and clinicians may be reluctant to take the risk of having to endure another relapse, and this makes the process of withdrawal even more difficult, since many people report that they benefit from having support from other people when they try to reduce medication. 46,53–57…”
Section: Relapsementioning
confidence: 99%
See 2 more Smart Citations